2006
DOI: 10.1016/j.physleta.2006.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Equations of motion, noncommutativity and quantization

Abstract: We study the relation between a given set of equations of motion in configuration space and a Poisson bracket. A Poisson structure is consistent with the equations of motion if the symplectic form satisfy some consistency conditions. When the symplectic structure is commutative these conditions are the Helmholtz integrability equations for the nonrestricted inverse problem of the calculus of variations [8]. We have found the corresponding consistency conditions for the symplectic noncommutative case.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…where A and C are defined through the symplectic form (15). In summary we conclude that the θ-deformed Helmholtz conditions (17) are in fact the Helmholtz conditions associated to a θ-deformed Newtonian system (24) where N and M are related with the symplectic form σ by the identification (26).…”
Section: Symplectic Formulation Of the Ncc And Helmholtz Conditionsmentioning
confidence: 65%
See 3 more Smart Citations
“…where A and C are defined through the symplectic form (15). In summary we conclude that the θ-deformed Helmholtz conditions (17) are in fact the Helmholtz conditions associated to a θ-deformed Newtonian system (24) where N and M are related with the symplectic form σ by the identification (26).…”
Section: Symplectic Formulation Of the Ncc And Helmholtz Conditionsmentioning
confidence: 65%
“…The aim of the present note is to extend our previous investigation [14] where we have studied the dynamical compatibility between a Poisson bracket and a given set of second order equations of motion. We have found that if the Poisson bracket is noncommutative…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Now it is required that the primary constraint Ω 1 be preserved in time under the action of the Hamiltonian H,π 9) where these brackets denote the standard Poisson bracket defined as,…”
Section: Introduction and Properties Of The Modelmentioning
confidence: 99%